RdJ detection tests to identify a unique MRSA clone of ST105-SCCmecII lineage and its variants disseminated in the metropolitan region of Rio de Janeiro - Esteves, Matheus Assis Côrtes; Viana, Alice Slotfeldt; Viçosa, Gabriela Nogueira; Botelho, Ana Maria Nunes; Moustafa, Ahmed M.; Mansoldo, Felipe Raposo Passos; Ferreira, Adriana Lucia Pires; Vermelho, Alane Beatriz; Ferreira-Carvalho, Bernadete Teixeira; Planet, Paul Joseph; Figueiredo, Agnes Marie Sá (Frontiers in Microbiology, 2023)
Hospital bloodstream infection (BSI) caused by methicillin-resistant Staphylococcus aureus (MRSA) is a major cause of morbidity and mortality and is frequently related to invasive procedures and medically complex patients. An important feature of MRSA is the clonal structure of its population. Specific MRSA clones may differ in their pathogenic, epidemiological, and antimicrobial resistance profiles. Whole-genome sequencing is currently the most robust and discriminatory technique for tracking hypervirulent/welladapted MRSA clones. However, it remains an expensive and time-consuming technique that requires specialized personnel. In this work, we describe a pangenome protocol, based on binary matrix (1,0) of open reading frames (ORFs), that can be used to quickly find diagnostic, apomorphic sequence mutations that can serve as biomarkers. We use this technique to create a diagnostic screen for MRSA isolates circulating in the Rio de Janeiro metropolitan area, the RdJ clone, which is prevalent in BSI. The method described here has 100% of specificity and sensitivity, eliminating the need to use genomic sequencing for clonal identification. The protocol used is relatively simple and all the steps, formulas and commands used are described in this work, such that this strategy can also be used to identify other MRSA clones and even clones from other bacterial species.